Health hazard evaluation in private dental practices: a survey in a province of northen Italy - Veronesi, L.; Bonanini, M.; Dall'Aglio, et al., P. (Acta Biomedica Atenei Parmensis, 2004)
The purpose of this questionnaire survey was to evaluate the knowledge and attitudes of private dental health care workers about cross-infection hazards through examination of practising behaviour in respect of infection control. A questionnaire was sent by mail to the private dentists operating in Parma province. The survey concerned 7 groups of questions about demographic data, personal protective equipment, immunization, sterilization and disinfection, waste disposal and occupationally acquired injuries, behaviour. Four hundred questionnaires were sent to the members of the Medical and Dentist College of Parma: 122 were returned and analysed (30.5%). Among the infectious diseases 45% of the interviewed think that the most dangerous diseases are Hepatitis B and C, followed by HIV infection (21.5%). The most used personal protective equipments are gloves (98%), masks (95%) and protective eyewear (94%). Sixty eighth per cent of the dentists treat HBV, HCV, HIV, TB, HSV suffering patients at the end of the working day. Twenty nine point 7% of them claim to have written protocols to follow in case of accident. Altogether the results show a good knowledge of the most important risks related to dentistry activity and of the main procedures for the infection control and management.